Respuesta :

For this system of equation I used substitution:

Step 1: Every time you see a y in the equation y = 2x - 1 replace it with -4x - 19

-4x - 19 = 2x - 1

Step 2: Isolate x

(-4x + 4x) - 19 = (2x + 4x) - 1

-19 = 6x - 1

-19 + 1 = 6x + (- 1 + 1)

-18 = 6x

x = -3

Step 3: To solve for y replace x in the equation y = 2x - 1 with -3

y = 2(-3) - 1

y = -6 - 1

y = -7

(-3, -7)

Check:

-7 = -4(-3) - 19

-7 = 12 - 19

-7 = -7 --------------------------------> Correct!

-7 = 2(-3) - 1

-7 = -6 - 1

-7 = -7 --------------------------------> Correct!

Hope this helped!

ACCESS MORE